THE ABILITY OF THE FOURTH SEMESTER STUDENTS OF POLITEKNIK TRI JAYA KRAMA MEDAN IN USING THE DIFFERENCE GERUND AND PRESENT PARTICIPLE - Rafika Purba (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2016)
Abstract The research deals with the using of gerund and present participle. The problems of the research are What is the extent of students’ ability in using the difference gerund and present participle and What are the second students’ difficulties of using gerund and present participle. The objective of the study are to know the extent of students’ ability in using the difference gerund and present participle and the difficulties of students in using the difference gerund and present participle. The research did in Politeknik Tri Jaya Krama Medan. In this section, the researcher took sample from the amount of the fourth semester students in Politeknik Tri Jaya Krama Medan, which only 94 ( ninety four ) students. The purpose of this research is to find out whether the students are able or unable in using the difference between Gerund and Present Participle. Keywords : Grammar, Gerund, Present Participle